2014
DOI: 10.1016/j.molcel.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Double Suppression of the Gα Protein Activity by RGS Proteins

Abstract: Regulator of G protein signaling (RGS) proteins accelerate GTP hydrolysis on G protein α subunits, restricting their activity downstream from G protein-coupled receptors. Here we identify Drosophila Double hit (Dhit) as a dual RGS regulator of Gαo. In addition to the conventional GTPase-activating action, Dhit possesses the guanine nucleotide dissociation inhibitor (GDI) activity, slowing the rate of GTP uptake by Gαo; both activities are mediated by the same RGS domain. These findings are recapitulated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 42 publications
3
90
0
Order By: Relevance
“…It has been reported that RGS16 and RGS18 interact with Ga i and inhibit its function [27][28][29]. Our results showed that RGS16 interacts with PAR2 in the presence of Ga i but not other Ga proteins.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that RGS16 and RGS18 interact with Ga i and inhibit its function [27][28][29]. Our results showed that RGS16 interacts with PAR2 in the presence of Ga i but not other Ga proteins.…”
Section: Discussionsupporting
confidence: 47%
“…It is noteworthy that both the GEF and GDI functions of GIV are mediated via the same evolutionarily conserved C-terminal short GBA motif, as reported previously in the case of the synthetic KB-752 peptide (14,15). Such a role is analogous to the bifunctional [GTPase-activating proteins (GAP) and GDI] role of the regulators of G protein signaling (or RGS) domain of Drosophila Double hit (Dhit) (32).…”
Section: Discussionmentioning
confidence: 59%
“…The high sequence homology in the GTP binding motif and P loop region between zebrafish Sec14l3 and human SEC14L2/SEC14L3/SEC14L4 (Figure 6A) suggests a GTPase activity of zebrafish Sec14l3. Then we adopted BODIPY-FL-GTPγS conventional assay and MESG-based single-turnover assay to detect the GTP binding and GTP hydrolysis activities of Sec14l3 (Lin et al, 2014; McEwen et al, 2001; Tõntson et al, 2012; Webb, 1992). It estimated the K diss and K hydr rate constants for Sec14l3 to be 0.298 ± 0.089 min −1 and 0.151 ± 0.025 min −1 respectively (Figure 6B–C).…”
Section: Resultsmentioning
confidence: 99%